An Investigation into the Factors Affecting the Bandwidth of Measured Leak Noise in Buried Plastic Water Pipes - Scussel, Oscar; Brennan, Michael J. [UNESP]; de Almeida, Fabricio C. L. [UNESP]; Iwanaga, Mauricio K. [UNESP]; Muggleton, Jennifer M.; Joseph, Phillip F.; Gao, Yan (Springer Nature, 2023)
Inspection and preservation of buried water pipelines is of importance in the modern world. The wastage of water due to leaks is a global problem and existing technologies/methods to detect leaks in buried pipelines still face challenges, such as how to predict the bandwidth of measured leak noise using acoustic correlators, and what are the main factors affecting this frequency range. The leak noise bandwidth is useful information for operators to know before carrying out tests in the field, and currently there is no practical way of predicting this frequency range. This paper presents an approach to predict the bandwidth and investigates the main factors affecting it such as the distance between the sensors, wave speed and attenuation of the fluid-dominated wave, which is the main carrier of leak noise. To achieve this, a water-pipe-soil-sensor model is represented in terms of filters, allowing an investigation into the corresponding physical/geometric characteristics that affect the bandwidth of the measured leak noise. It is shown that the dominant factors are the material and geometry of the pipe, the properties of the surrounding soil and the type of transducer used.
Keywords: Buried pipelines; Leak noise bandwidth; Vibro-acoustic correlators; Water distribution systems